Lessons drawn from research utilization in the maternal iodine supplementation policy development in Thailand - Tonmukayakul Utsana; Velasco Román; Tantivess Sripen; Teerawattananon Yot (BMC, 2012)
Abstract In this paper, the authors share their experience on evidence utilization in the development of Thailand's maternal iodine supplementation policy in 2009-2010. Observations and reflections on their experience of engaging with research for policymaking are illustrated. The case study indicates that rapid approaches in conducting research, namely a targeted literature review and cross-sectional survey of professionals' opinions and current practices were efficient in achieving the timeliness of evidence provision. In addition pro-activity, trust and interaction between researchers and policymakers enhanced the research-policy integration. The Thai experience may be useful for other developing countries which pursue evidence-informed policymaking, despite differences in the health system context.